Handbook of research on management and strategies for digital enterprise transformation - Sandhu, Kamaljeet, 1970- (Advances in e-business research series., 2021)
"This book focuses on theoretical models, methodologies, best practices, and empirical and qualitative studies on digital enterprise transformation"--